The effect of great strength and speed exercises in developing the muscular ability of young handball players - Hkem Mohamed, Sardar; Mohammed Headan, Hussam (International Journal of Psychosocial Rehabilitation, 2020)
Sports training is one of the most important sciences in the sports field because of its great role in supporting the training process and developing the training status of the athlete by finding the best methods to upgrade the physical, skill, and planning level and reach to achieve training goals and achievement. The concept of physical abilities in the sports field means the association of two different physical traits with each other, which results in the correlation of a physical trait that combines the characteristics of these two physical traits. For example, the ability of the rapid force represented by the explosive force and the force characterized by speed is a mix between the maximum force and the speed So, the athlete must have these two characteristics in order for him to show perfect fast strength ideally, and muscle groups that have fast ability are characterized by high muscle tension characterized by rapid contractility and muscle relaxation.